Expression quantitative trait loci for ETV4 and MEOX1 are associated with adult asthma in Japanese populations - Yohei Yatagai (Nature Portfolio, 2021)
Abstract ETS variant transcription factor 4 (ETV4) is a recently identified transcription factor that regulates gene expression-based biomarkers of asthma and IL6 production in an airway epithelial cell line. Given that ETV4 has not yet been implicated in asthma genetics, we performed genetic association studies of adult asthma in the ETV4 region using two independent Japanese cohorts (a total of 1532 controls and 783 cases). SNPs located between ETV4 and mesenchyme homeobox 1 (MEOX1) were significantly associated with adult asthma, including rs4792901 and rs2880540 (P = 5.63E−5 and 2.77E−5, respectively). The CC haplotype of these two SNPs was also significantly associated with adult asthma (P = 8.43E−7). Even when both SNPs were included in a logistic regression model, the association of either rs4792901 or rs2880540 remained significant (P = 0.013 or 0.007, respectively), suggesting that the two SNPs may have independent effects on the development of asthma. Both SNPs were expression quantitative trait loci, and the asthma risk alleles at both SNPs were correlated with increased levels of ETV4 mRNA expression. In addition, the asthma risk allele at rs4792901 was associated with increased serum IL6 levels (P = 0.041) in 651 healthy adults. Our findings imply that ETV4 is involved in the pathogenesis of asthma, possibly through the heightened production of IL6.